Urgensi Keberadaan Pengaturan Larangan Kepemilikan Tanah Secara Absentee dalam Reforma Agraria - Prawita, Metrika; Istislam, Istislam; Laila, Fathul (Jurnal Ilmiah Pendidikan Pancasila dan Kewarganegaraan, 2021)
This study aimed to analyze the regulation on Absentee land ownership, the purpose of Absentee land ownership regulation, and the urgency and relevance of the regulation on Absentee land ownership in agrarian reform. The type of research used in this study was normative juridical with a positivist legalistic approach. The regulation on the prohibition of absentee land ownership was regulated in additional rules contained in Articles 3A to 3E of Government Regulation Number 41 of 1964 and further reaffirmed by Regulation of the Minister of Agrarian Affairs and Spatial Planning/Head of BPN Number 18 of 2016 concerning Control of Agricultural Land Control. The purpose of the regulation on the prohibition of absentee land ownership was so that the local community could enjoy the results obtained from land management. The urgency and relevance of the regulation on the prohibition of absentee land ownership at the time of agrarian reform could not be carried out effectively because there was no specific regulation governing Absentee land. Thus, it was necessary to review and even eliminate some regulations no longer by current and future developments.